It's not just who you know : transform your life (and your organization) by turning colleagues and contacts into lasting, genuine relationships - Spaulding, Tommy (New York : Broadway Books, 2010)
Spaulding believes success-- in business and in life-- is all about relationships. He takes Dale Carnegie's classic philosophy to the next level, showing how by developing deeper relationships through giving to others and putting them first, we benefit as well
Standing on Carnegie's shoulders -- pt. 1. Relationship discoveries : An unlikely prodigy ; The bartender ; Relationship economics -- pt. 2. How to build relationship capital : The five floors of relationships ; What you do ; Don't shoot the moose ; Do your homework ; Breaking the ice, and stirring it up ; Back of the business card ; Leveraging philanthropy ; Never kiss on the first date ; Don't be a chirping bird ; Pardon me while I talk to your wife ; Relentless communication ; Play chess, not monopoly ; Seek advice, not business ; He's just not that into me -- pt. 3. The power of netgiving : Making business personal ; Beyond networking ; Authenticity: making relationships real ; Empathy: setting a cornerstone for trust ; Vulnerability: opening a window into your inner world ; Confidentiality: living the law of the vault ; Curiosity: the power of asking questions ; Generosity: Acting on your awareness ; Humility: the gift of perspective ; Humor: living with levity ; Gratitude: the art of being thankful -- pt. 4. Relationshift: life in the penthouse : Journey to the penthouse ; The ultimate Middel man ; Moore than meets the eye ; Collecting what matters ; Fifth floor givers ; Living give/get from the outside/in ; Elevation: advance, link, and lift ; Serving the stakeholders ; Warnings -- pt. 5. Putting purpose first : Relationships + vision = impact ; Orion's Belt ; How to make the world spin better
Includes bibliographical references and index
Keywords: Success in business; Success; Interpersonal relations